Costs as an economic category exposed to risk - Nowak, Edward (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Costs are one of the fundamental economic categories characterising the achievements of business entities. The costs incurred by companies stem from the coexistence of various factors, whose occurrence is affected by the volatility of the external and internal environment. Therefore, costs are inherently connected with the risk that the incurred costs will differ from those assumed and postulated. Costs can thus be seen as an economic value subject to risk. This article concerns the risks of business entities, associated with incurring costs. The article presents the nature and sources of cost risk and the impact of various types of economic risk on the costs. It also presents the essence of risk management associated with costs incurred by the company. Particular attention was paid to assessing the level of cost risk on the basis of the deviations of incurred values from the postulated ones
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 195-202
Keywords: risk; cost; risk measurement; cost risk; cost management; ryzyko; koszty; pomiar ryzyka; ryzyko kosztów; zarządzanie kosztami